Ultra-thin Glass Film Coated with Graphene: A New Material for Spontaneous Emission Enhancement of Quantum Emitter - Sun, Lu; Jiang, Chun (Nano-Micro Letters, 2015)
We propose an ultra-thin glass film coated with graphene as a new kind of surrounding material which can greatly enhance spontaneous emission rate (SER) of dipole emitter embedded in it. With properly designed parameters, numerical results show that SER-enhanced factors as high as 1.286 × 106 can be achieved. The influences of glass film thickness and chemical potential/doping level of graphene on spontaneous emission enhancement are also studied in this paper. A comparison is made between graphene and other coating materials such as gold and silver to see their performances in SER enhancement.